11. STUDY ON METABOLIC SYNDTOME IN OSTEOPOROSIS PATIENTS AT NGHE AN GENERAL FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Determine the proportion of patients with metabolic syndrome and the relationship between components of metabolic syndrome and osteoporosis patients at Nghe An General Friendship Hospital.Research method: Cross-sectional descriptive study design was conducted on 102 osteoporosis patients examined at Rheumatology clinic and Rheumatology Department, Nghe An General Friendship Hospital from January 2023 to March 2024.Results: The majority of patients over 70 years old is 58.8%, average age 71.26 ± 0.96 years old; women account for 84,3%. The prevalence of metabolic syndrome is 72.5%, the proportion of women with Metabolic Syndrome is lower than men with MS (72.1% and 75%). There is a relationship between some components of the metabolic syndrome such as increased blood glucose, high blood pressure and obesity between two groups of treated osteoporosis patients and those without treatment.Conclusion: Patients with osteoporosis have a high rate of metabolic syndrome, and hypertension is one of the comorbidities with the highest rate. Osteoporosis and metabolic syndrome are two very common co-morbidities, therefore, more detailed examination and evaluation is needed when both diseases are present, especially in elderly patients.
Keywords: Metabolic syndrome, osteoporosis, Nghe An General Friendship Hospital.